Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 125800 by TITA last updated on 13/Dec/20

Commented by TITA last updated on 13/Dec/20

prove

prove

Commented by liberty last updated on 14/Dec/20

b^2 x^2 −a^2 (mx+c)^2 =a^2 b^2   b^2 x^2 −a^2 (m^2 x^2 +2mcx+c^2 )−a^2 b^2 =0  (b^2 −a^2 m^2 )x^2 −2a^2 mcx−(a^2 c^2 +a^2 b^2 )=0  D=0 ⇒ 4a^4 m^2 c^2 +4(b^2 −a^2 m^2 )(a^2 c^2 +a^2 b^2 )=0  ⇒a^4 m^2 c^2 +b^2 a^2 c^2 +a^2 b^4 −a^4 m^2 c^2 −a^4 m^2 b^2 =0  ⇒b^2 a^2 c^2 +a^2 b^4 −a^4 m^2 b^2 =0  ⇒a^2 b^2 (c^2 +b^2 −a^2 m^2 )=0 ; a^2 ≠ 0 ∧b^2 ≠0  ⇒c^2  =a^2 m^2 −b^2  ∧ c = (√(a^2 m^2 −b^2 )) .

b2x2a2(mx+c)2=a2b2b2x2a2(m2x2+2mcx+c2)a2b2=0(b2a2m2)x22a2mcx(a2c2+a2b2)=0D=04a4m2c2+4(b2a2m2)(a2c2+a2b2)=0a4m2c2+b2a2c2+a2b4a4m2c2a4m2b2=0b2a2c2+a2b4a4m2b2=0a2b2(c2+b2a2m2)=0;a20b20c2=a2m2b2c=a2m2b2.

Commented by liberty last updated on 14/Dec/20

other way ⇒ gradient tangent line   ((2x)/a^2 )−((2yy′)/b^2 ) = 0 ; b^2 x=a^2 y.y′  ⇒y′ = ((b^2 x)/(a^2 y)) = m ⇒x=((ma^2 y)/b^2 )  substitute in to hyperbola  (((m^2 a^4 y^2 )/b^4 )/a^2 ) − (y^2 /b^2 ) = 1 ; (((m^2 a^2 −b^2 )y^2 )/b^4 )=1  y^2 =(b^4 /(m^2 a^2 −b^2 )) → { ((y=(b^2 /( (√(m^2 a^2 −b^2 )))))),((y=−(b^2 /( (√(m^2 a^2 −b^2 )))))) :}  contact point ⇒x=((ma^2 (−(b^2 /( (√(m^2 a^2 −c^2 ))))))/b^2 )=−((ma^2 )/( (√(m^2 a^2 −b^2 ))))  thus −(b^2 /( (√(m^2 a^2 −b^2 )))) = ((−m^2 a^2 )/( (√(m^2 a^2 −b^2 )))) + c    c = ((m^2 a^2 −b^2 )/( (√(m^2 a^2 −b^2 )))) = (√(m^2 a^2 −b^2 ))

otherwaygradienttangentline2xa22yyb2=0;b2x=a2y.yy=b2xa2y=mx=ma2yb2substituteintohyperbolam2a4y2b4a2y2b2=1;(m2a2b2)y2b4=1y2=b4m2a2b2{y=b2m2a2b2y=b2m2a2b2contactpointx=ma2(b2m2a2c2)b2=ma2m2a2b2thusb2m2a2b2=m2a2m2a2b2+cc=m2a2b2m2a2b2=m2a2b2

Commented by TITA last updated on 14/Dec/20

thamks guys

thamksguys

Commented by TITA last updated on 14/Dec/20

thanks

thanks

Answered by TITA last updated on 13/Dec/20

please help

pleasehelp

Answered by peter frank last updated on 14/Dec/20

y=mx+c  (x^2 /a^2 )−(y^2 /b^2 )=1  (x^2 /a^2 )−(((mx+c)^2 )/b^2 )=1  put  discrimint =0  ...

y=mx+cx2a2y2b2=1x2a2(mx+c)2b2=1putdiscrimint=0...

Answered by peter frank last updated on 14/Dec/20

Terms of Service

Privacy Policy

Contact: info@tinkutara.com